Security policy integration based on role-based access control model in healthcare collaborative environments - Teo, Poh Kuang; Ibrahim, Hamidah (Universiti Utara Malaysia, 2010)
Recently research is focused on security policy integration and conflict reconciliation among various healthcare organizations. However, challenging security and privacy risks issues still arisen during sharing sensitive patient data in different large distributed organizations. In this paper, we proposed an approach for integrating security policies based on Role-Based Access Control (RBAC) policy model that supports dynamic constraint rules and meta data information, reduces policy redundancy and resolves conflicts based on the types of policy redundancy and conflict. We believe this work can support dynamic updates and control policies in collaborative environments.